Violence against healthcare workers during the COVID-19 pandemic: a cross-sectional survey at Cairo University Hospital - Seddik, Salma Abdelrehim; Abdelhai, Rehab; Aboushady, Ahmed Taha; Nawwar, Ahmed Essam; El Essawy, Rania Assem; Hegazy, Amira Aly (Frontiers in Public Health, 2023)
Healthcare workers have a significant chance of experiencing violence, with physical violence impacting anywhere from 8% to 38% of healthcare professionals throughout their careers. Besides physical abuse, many healthcare workers are subject to verbal aggression or threats, with patients and visitors being the most frequent sources of such incidents. This research examines the work atmosphere of healthcare professionals at Kasr Al-Ainy University Hospital in Cairo, Egypt, during the pandemic. The study aims to evaluate the frequency of violence towards healthcare workers and health professionals training through a cross-sectional survey conducted among them. The research was conducted on Egyptian healthcare workers over six months, from November 2020 until the end of January 2021, using convenience sampling in a cross-sectional study.Over half of the respondents reported experiencing violence. Among those who experienced violence, 93% reported verbal aggression, 43% reported physical and verbal abuse, and 59% claimed that violence increased during the pandemic. Additionally, 97% of those who experienced violence reported it occurring within the four months following the survey. About 42.5% of the respondents were female, and nearly 65% were over 30. 82% of the respondents did not receive training on handling violence while performing their job.This study highlights the high prevalence of verbal assaults in healthcare settings, primarily by patients' families or acquaintances. Despite reporting such incidents, most respondents did not see any significant government action. Furthermore, the COVID-19 pandemic did not significantly change the frequency of violent incidents, indicating that the root causes of violence are systemic and extend beyond the pandemic. These findings underscore the need for systemic changes in healthcare organizations to address and prevent violence against healthcare workers.